2012
DOI: 10.1063/1.3700676
|View full text |Cite
|
Sign up to set email alerts
|

Event-by-event hydrodynamics for heavy-ion collisions

Abstract: We compare v2/{\epsilon}2 and v3/{\epsilon}3 from single-shot and event-by-event (2+1)-dimensional hydrodynamic calculations and discuss the validity of using single-shot calculations as substitutes for event-by-event calculations. Further we present a proof- of-concept calculation demonstrating that v2 and v3 together can be used to strongly reduce initial condition ambiguities.Comment: 3 pages, 2 figures. Contribution to the proceedings for 19th Particles & Nuclei International Conference (PANIC11

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
(11 reference statements)
0
24
0
Order By: Relevance
“…3 In Fig. 4.5 of Zhi Qiu's Ph.D. thesis [31] it was shown that this sign change is genuinely related with a sign change between the final hydrodynamic flow plane and initial participant plane correlators, and not qualitatively changed by mode-mixing effects inherent in the Cooper-Frye formula for computing the momentum distributions and their anisotropies at freeze-out [30]. This led the authors of Ref.…”
Section: "Mode Coupling" Between the Initial Eccentricitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In Fig. 4.5 of Zhi Qiu's Ph.D. thesis [31] it was shown that this sign change is genuinely related with a sign change between the final hydrodynamic flow plane and initial participant plane correlators, and not qualitatively changed by mode-mixing effects inherent in the Cooper-Frye formula for computing the momentum distributions and their anisotropies at freeze-out [30]. This led the authors of Ref.…”
Section: "Mode Coupling" Between the Initial Eccentricitiesmentioning
confidence: 99%
“…This observation is consistent with Refs. [17][18][19]31] where it was found that hydrodynamic evolution changes the sign of the correlations between the initial participant planes and the final flow planes that are associated with these coupling coefficients. 3 In Fig.…”
Section: "Mode Coupling" Between the Initial Eccentricitiesmentioning
confidence: 99%
“…In particular, comprehensive studies have been devoted to fluctuations of the average transverse momentum p T , both from the theoretical [34][35][36][37] and experimental side [38][39][40][41], as these fluctuations may reflect critical phenomena expected at the phase transition. Much progress has been made in understanding the response to initial fluctuations [11,[42][43][44][45][46]: typically, elliptic flow is proportional to the initial eccentricity [7]; triangular flow is proportional to the initial triangularity [10]; finally, p t fluctuations arise as a natural consequence of initial-state (size) fluctuations [47]. Eventually, the study of fluctuations essentially boils down to the study of the initial fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has now been paid to fluctuations of the anisotropic flows of final hadrons due to the fluctuations in the initial states of heavy-ion collisions, such as the fluctuations of nucleon positions and color charges inside colliding nuclei and multiplicities of initial parton production [10]. One of the most interesting consequences of initial-state fluctuations is the presence of elliptic flow in the most central nucleus-nucleus collisions, and finite odd harmonic flows in the final-state azimuthal distributions [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The elliptic, triangular and other higher-order harmonic flows have been measured in Au+Au collisions at RHIC and Pb+Pb collisions at the LHC [27][28][29].…”
Section: Introductionmentioning
confidence: 99%